E-DIAGNOSIS PENYAKIT PADA TANAMAN SAWIT MENGGUNAKAN METODE CERTAINTY FACTOR - Erni Yusnita Pratama; Oris Krianto Sulaiman; Khairuddin Nasution (LPPM Universitas Deli Sumatera, 2021)
Oil palm is one of the plants that has its own charm in the community. Currently, oil palm plantations in Indonesia are growing very rapidly, especially in the province of Riau. Oil palm is grown and cultivated almost all over the archipelago, whether it is privately owned or owned by a company. This plant contains many properties that make the demand for oil palm continue to increase. An expert system is a branch of artificial intelligence that uses specialized knowledge to solve problems at the expert level. One application of the expert system is in the field of plantations to diagnose diseases in plants. In this study, the design and manufacture of an expert system used to help diagnose a disease in oil palm plants and determine suggestions or treatment solutions for oil palm plants. The final result of this paper is an expert system for diagnosing oil palm plant diseases along with the diagnostic value of the diagnosed disease which shows the level of system confidence in the disease and suggestions or treatment solutions for the oil palm plant. Keywords: Expert system; Certainty Factor; Palm Plant Disease